PENGARUH ENTREPRENEURIAL SELF EFFICACY DAN MOTIVASI (NEED FOR ACHIEVEMENT) TERHADAP KINERJA UMKM PADA SEKTOR INDUSTRI OLAHAN DI KABUPATEN TABALONG - Liza Putri Wiharti; Zakhyadi Ariffin; Dahniar Dahniar (Al-Iqtishadiyah: Ekonomi Syariah dan Hukum Ekonomi Syariah, 2017)
This study aims to identify and analyze the influence of entrepreneurial self efficeacy (x1) and motivation (x2) as independent variabels to the performance of UMKM (Y) as the dependent variable on the processed sector in Tabalong RegencyThis research method used questionnaires to the perpetrators of MSMEs in the processed sector in Tabalong Regency as many as 82 people. Samples were taken using a purposive sampling technique. Measurement variable used likert scale technique eith the scale weight 1 to 5. To see the effects of variable X to Variable Y using multiple linear regression analysis technique.The result of this research conludes that thare are positive and significant effects from each independent variable to dependent variable. From the research results, it can be seen that the highest percentage is the Motivation compared to Enterpreneirial Self Efficacy.